2016
DOI: 10.1063/1.4971402
|View full text |Cite
|
Sign up to set email alerts
|

Role of oxygen and nitrogen in n-type microcrystalline silicon carbide grown by hot wire chemical vapor deposition

Abstract: N-type microcrystalline silicon carbide (μc-SiC:H(n)) deposited by hot wire chemical vapor deposition provides advantageous opto-electronic properties for window layer material in silicon-based thin-film solar cells and silicon heterojunction solar cells. So far, it is known that the dark conductivity (σd) increases with the increase in the crystallinity of μc-SiC:H(n)films. However, due to the fact that no active doping source is used, the mechanism of electrical transport in these films is still under debate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…These results corroborate with the RBS analysis presented in Figure 1a. In addition, Pomaska et al presented studies on the unintentional doping by oxygen contamination where they demonstrated that the oxygen incorporation was influenced the microstructural, electronic, and optical properties of the SiC films [39]. It has been shown that oxygen incorporation during film deposition increases the crystallinity of SiC films, consistent with findings observed in this work.…”
Section: Resultssupporting
confidence: 87%
“…These results corroborate with the RBS analysis presented in Figure 1a. In addition, Pomaska et al presented studies on the unintentional doping by oxygen contamination where they demonstrated that the oxygen incorporation was influenced the microstructural, electronic, and optical properties of the SiC films [39]. It has been shown that oxygen incorporation during film deposition increases the crystallinity of SiC films, consistent with findings observed in this work.…”
Section: Resultssupporting
confidence: 87%
“…Among various ways available, ion-beam implantation is a very reliable and popular technique to incorporate impurities in a host lattice [1][2][3] as it provides controllable selective area doping in the target materials [4]. The most widely used implanted defects in semiconductors include P, B, As [5][6][7][8][9] and Si + [10,11] implanted thermal oxide films on crystalline Si for photoluminiscence, modified refractive index and optical waveguides, O and N in SiC [12], P [13], B [14], Si [15][16][17] and Er [18,19] in SiO 2 , Au [20], Cu [21] in SiO 2 , Pd in Si [22] and As in GaAs [23] for tuning optical and physical properties. Doped rock-salt oxides (for example MgO) have been studied extensively [24][25][26][27][28][29][30][31][32][33][34][35] for their applications in optical and magnetic sensors, switching devices and as dilute magnetic semiconductors [36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…Kultayeva et al 27 reported a difference of four orders of magnitude in the electrical resistivity of N 2 -doped (2.1 × 10 -1 Ω.cm) and undoped (1.2 × 10 3 Ω⋅cm) SiC at the same porosity of 62%. In addition to N 2 , 122-126 O 2 , 126,127 Al, [128][129][130][131] B, 131,132 V, 133,134 Be, 131 Ga, 122 Sc, 135,136 P, 123,124,137 C, 127 etc. are soluble in the SiC lattice.…”
Section: Doping Of Soluble Atomsmentioning
confidence: 99%